Relationships between self-efficacy and learning approaches as perceived by computer science students - Laitinen, Satu; Christopoulos, Athanasios; Laitinen, Petteri; Nieminen, Valtteri (Frontiers in Education, 2024)
Optimising learning outcomes in university students necessitates an understanding of the processes that drive high-quality learning outcomes. This study investigates the motivational factors and learning methodologies perceived by computer science students during an introductory course. A crosssectional study was conducted with 171 computer science students asked to complete a psychometric instrument ("Study Skills Inventory for Students") during the first year of their university studies. Two major theoretical frameworks in educational psychology, namely students' self-efficacy and learning approaches were tested relative to a factor structure obtained from learning situations. The findings supported self-efficacy and three learning approaches among computer science students. Models for deep, surface, and strategic learning approaches suggest that students with higher self-efficacy tend to adopt a deeper approach to learning. Conversely, students with lower self-efficacy were more inclined toward surface learning methods. Furthermore, a link was identified between strategic learning approaches and students' experiences within their learning environments. The results substantiate earlier research and align with learning approach theories. The findings indicated that, in higher education settings, focus should be directed toward understanding the motivational factors influencing students and their learning approaches for educational outcomes.